Seed germination and methods to break seed dormancy in Sri Lankan endemic wild rice species Oryza rhizomatis - Gowri, R. (University of Jaffna, 2022)
Wild species Oryza rhizomatis which has been reported only from Sri Lanka. Therefore, it is endemic to the country and was discovered in 1989 for the first time. It is distributed in the dry zone of Sri Lanka during the period of December to May. O. rhizomatis is adapted to specific areas and highly resistant to drought, temperature, soil type and water quality. Studies related to assessment of viability, germination potential and dormancy breaking methods of O. rhizomatis were carried out to check the viability and germination potential of the seeds of this species and compared with commercial rice cultivar Bg352.Tetrazolium chloride test revealed that O. rhizomatis seeds used in the study were found to be 80% viable. However, only 5% of seeds germinated under the optimum laboratory conditions. From this study, it was confirmed that O. rhizomatis seeds have dormancy thus proper treatments are required to break the dormancy as compared to Bg352.This study revealed that the mechanical, chemical and heat treatment as a combination is the most appropriate method for breaking the dormancy to get maximum germination of seeds of O. rhizomatis.
Keywords: Bg352; Germination; Dormancy; Oryza rhizomatis; Tetrazolium chloride; Viability